2018
DOI: 10.1371/journal.pone.0203115
|View full text |Cite
|
Sign up to set email alerts
|

Unkept promises of cognitive styles: A new look at old measurements

Abstract: Cognitive style is thought to be a stable marker of one’s way to approach mental operations. While of wide interest over the last decades, its operationalization remains a challenge. The literature indicates that cognitive styles assessed via i) questionnaires are predicted by personality and ii) performance tests (e.g., Group Embedded Figures Test; GEFT) are related to general intelligence. In the first study, we tested the psychometric relationship between the Cognitive Style Index questionnaire (CSI) and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The results raise questions of a) the validity of the concept of cognitive styles and b) its dichotomous nature. In terms of a), Cuneo et al [65] tested the discriminant validity of methods for analytic-holistic style diagnostics and found that questionnaire methods overlapped with personality and that maximum performance methods (Group Embedded Figures Test) overlapped with intelligence. Further research should test the construct, concurrent and discriminant validity of cognitive styles, especially in relation to personality and intelligence.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The results raise questions of a) the validity of the concept of cognitive styles and b) its dichotomous nature. In terms of a), Cuneo et al [65] tested the discriminant validity of methods for analytic-holistic style diagnostics and found that questionnaire methods overlapped with personality and that maximum performance methods (Group Embedded Figures Test) overlapped with intelligence. Further research should test the construct, concurrent and discriminant validity of cognitive styles, especially in relation to personality and intelligence.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Specifically, on the one hand, the disembedding ability allows people to memorize structural object characteristics which enabled a greater differentiation in perceptual functioning and as a consequence a better ability in recognizing objects, that is, it permits people to extract salient information from the surrounding environment. On the other hand, the perspectivism ability allows people to recognize visual perspectives other than those of the learned path, that is, it permits to adopt other people's perspective (e.g., Witkin and Goodenough 1977;Cuneo et al 2018). It appears clear that both disembedding and perspectivism underlie the ability to perform changes of perspective and updating spatial information being typically associated with FI people (Witkin and Goodenough 1977).…”
Section: Introductionmentioning
confidence: 99%
“…This cutoff is similar to, but slightly more conservative than, the widely used criterion of 0.30 (Jackson, 1976 ; Johnson, 2005 ). PR is measured by dividing the data into equivalent halves and creating parallel vectors for each factor (Cuneo et al, 2018 ; Jackson, 1976 ). The correlation between these vectors represents a participant’s PR.…”
Section: Study 1: Methodsmentioning
confidence: 99%